2011
DOI: 10.1371/journal.pone.0021923
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoporin Mediated Nuclear Positioning and Silencing of HMR

Abstract: The organization of chromatin domains in the nucleus is an important factor in gene regulation. In eukaryotic nuclei, transcriptionally silenced chromatin clusters at the nuclear periphery while transcriptionally poised chromatin resides in the nuclear interior. Recent studies suggest that nuclear pore proteins (NUPs) recruit loci to nuclear pores to aid in insulation of genes from silencing and during gene activation. We investigated the role of NUPs at a native yeast insulator and show that while NUPs locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 62 publications
(118 reference statements)
3
41
0
Order By: Relevance
“…Intriguingly, mutations in nuclear pore constituents affect both gene activation and repression (Dilworth et al 2005;Therizols et al 2006;Ruben et al 2011). This dual role does not appear to stem from the boundary activity of nuclear pore proteins, as reported by Ishii et al (2002).…”
Section: Boundaries Between Active and Inactive Domainsmentioning
confidence: 78%
See 3 more Smart Citations
“…Intriguingly, mutations in nuclear pore constituents affect both gene activation and repression (Dilworth et al 2005;Therizols et al 2006;Ruben et al 2011). This dual role does not appear to stem from the boundary activity of nuclear pore proteins, as reported by Ishii et al (2002).…”
Section: Boundaries Between Active and Inactive Domainsmentioning
confidence: 78%
“…This dual role does not appear to stem from the boundary activity of nuclear pore proteins, as reported by Ishii et al (2002). Indeed, it was shown that, despite the fact that nuclear pore proteins can bind the native tDNA insulator adjacent to HMR, the loss of their binding did not compromise insulator activity, even though they contributed to silencing at this locus (Ruben et al 2011). To reconcile the apparently conflicting role between NPCs and repressive telomeric foci, one might propose that the impact of NPCs on gene expression is not simply pore or position dependent, but depends on the binding of transactivators or repressors to cis-acting elements (Ruben et al 2011).…”
Section: Boundaries Between Active and Inactive Domainsmentioning
confidence: 79%
See 2 more Smart Citations
“…Several other studies have shown an association of NPCs with silenced genomic regions and chromatin boundary. Data from yeast and Drosophila revealed heterochromatin association with stable Nups, such as Nup100 or Nup84 (Galy et al, 2000;Ruben et al, 2011;Van de Vosse et al, 2013). In human HeLa cells, ChIP analysis of Nup93 also demonstrated that Nup93 interactions include silent gene regions marked by repressive histone modifications (Brown et al, 2008).…”
Section: Introductionmentioning
confidence: 99%